Increasing Community Capabilities In First Aid For Drowning People Through Basic Life Support - Kamesyworo; Eka Haryanti (Journal of Applied Nursing and Health, 2022)
Background: It predicted that trauma or accidents would be the second leading cause of death after heart disease. Most accidents occur in public places and in the community. One of these accidents occurred in water areas, such as the Lematang River, Lahat Regency. This training aims to provide the ability to the community so they can provide first aid to victims to avoid death and disability. This training aims to determine the level of community knowledge in Perigi Village, Pulau Pinang District, and Lahat Regency about essential life support Methods: The method of activity that will be used is Basic Life Support training. Participants will be given material about trauma, emergencies, and first aid methods with Basic Life Support (BHD). In connection with the importance of doing essential life support quickly on the survival rate of drowning sufferers, everyone should be trained to carry out basic life support measures. Basic life support measures taken by people in the vicinity of out-of-hospital sufferers immediately after the incident can increase the patient's survival rate Results: From the results of the training carried out in Perigi village, Pulau Pinang sub-district, the results obtained were The level of education is very influential on the success rate of this training. In most communities, more than 60% have upper secondary education. It was found that the community had been able to carry out first aid for drowning people with the Basic Life Support technique of 68.6%. Conclusion: It is essential to provide basic life support to the community to improve community safety and capacity, so the community must carry out regular training